2007
DOI: 10.1002/ijc.22654
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of ATBF1 regulates MUC5AC transcription in gastric cancer

Abstract: Human gastric epithelium has a unique mucin gene expression pattern, which becomes markedly altered in gastrointestinal disorder. This alteration in mucin expression, including the mucin MUC5AC, may be related to the development and prognosis of gastric cancers, and MUC5AC-positive gastric cancer has been reported to be poor prognosis. However, the molecular mechanism of MUC5AC transcriptional regulation has not been fully elucidated. AT motif-binding factor 1 (ATBF1) is a homeotic transcriptional regulatory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Sp1 and Gli are reported to enhance MUC5AC expression in human lung-epithelial and pancreatic cancer cells, respectively [24], [25]. Contrastively, ATBF1 is negatively regulate MUC5AC expression in human gastric cancer cells [26], In spite of these results, molecular mechanisms of MUC5AC expression in human gastrointestinal cells have not been fully elucidated. In the present study, we identified 15 bp sequence in human MUC5AC 5′-flanking region which plays an important role in MUC5AC expression in gastrointestinal cancer cells, and also found that the region contains a putative Gli-binding site which does not coincide with previous report [25].…”
Section: Introductionmentioning
confidence: 99%
“…Sp1 and Gli are reported to enhance MUC5AC expression in human lung-epithelial and pancreatic cancer cells, respectively [24], [25]. Contrastively, ATBF1 is negatively regulate MUC5AC expression in human gastric cancer cells [26], In spite of these results, molecular mechanisms of MUC5AC expression in human gastrointestinal cells have not been fully elucidated. In the present study, we identified 15 bp sequence in human MUC5AC 5′-flanking region which plays an important role in MUC5AC expression in gastrointestinal cancer cells, and also found that the region contains a putative Gli-binding site which does not coincide with previous report [25].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study investigating the subcellular localization of ATBF1 in gastric cancer, ATBF1 was demonstrated to bind to the AT motif in the promoter region of the mucin 5AC gene and negatively regulate its transcription (8). In addition, ATBF1 was observed to translocate to the nucleus by forming a complex with runt domain transcription factor 3 (RUNX3), in response to transforming growth factor (TGF)-β signal transduction (9).…”
Section: Introductionmentioning
confidence: 99%
“…Prunetin [27] and wogonin [28] are associated with the inhibition of MUC5AC mucin by the inhibition of the NF- κ B signaling pathway. In the stomach cancers and atrophic gastritis with Helicobacter pylori infection, it has been reported that SOX2 as a SRY-related HMG box protein and AT motif-binding factor 1 (ATBF-1) are associated with the regulation of MUC5AC expression [2931]. Further studies also may be needed to clarify the regulation of MUC5AC expression by TNF- α , the above-mentioned factors, or other ones.…”
Section: Discussionmentioning
confidence: 99%